2022
DOI: 10.1111/srt.13198
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency ultrasound features in vulvar lichen sclerosus and correlation with histopathology

Abstract: Background: Vulvar lichen sclerosus (VLS) is a chronic inflammatory disease initially involving anogenital areas. Noninvasive assessment is essential for precise management in VLS. We aim to analyze high-frequency ultrasound (HFUS) features and correlate HFUS with histopathological changes. Materials and methods: Forty patients with histopathologically confirmed VLS lesions were retrospectively identified from August 2020 to September 2021. The clinical manifestations, dermoscopic images as well as both 20 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In the comparisons of both subjective improvement and clinical efficacy, the response of LSC to laser therapy was more favorable (21)(22)(23). Borghi et al found that patients with lichen sclerosus were often associated with other autoimmune disorders (24).…”
Section: Discussionmentioning
confidence: 99%
“…In the comparisons of both subjective improvement and clinical efficacy, the response of LSC to laser therapy was more favorable (21)(22)(23). Borghi et al found that patients with lichen sclerosus were often associated with other autoimmune disorders (24).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory diseases represent a novel new frontier for the use of HRUS, which have been applied in the assessment and monitoring of psoriasis, dermatitis, vulvar lichen sclerosus and collagen vascular disease. 38,39 It can aid in diagnosis, quantification of disease severity, tracking of progression and assessment of response to treatment. 40 This capability provides critical data for personalized patient management and evaluation of therapeutic effectiveness.…”
Section: N Fl a M M Atory Dise Ase Smentioning
confidence: 99%